Satisfaction of Students with the Quality of Educational Services at Technical University - D. V. Maltsev; D. S. Repetskiy (Высшее образование в России)
Improving the quality of educational services is impossible without a detailed analysis of student satisfaction. Identifying weaknesses in the educational process and socio-cultural environment, as well as evaluating the dynamics of satisfaction in recent years will help to formulate a roadmap for managing the quality of education. The research was conducted at Perm Polytechnic University which is typical, therefore the findings of the research can be considered as representative.The article analyzes the results of a survey of 1126 full-time students, which was about 12% of the contingent (full-time). The sample is presented for all structural divisions: faculties and branches, as well as the content of questionnaires on blocks of questions. The results of the level of satisfaction with the quality of educational activities are analyzed, in particular: the content of educational programs, the implementation of educational programs, the conditions for ensuring the educational process, the quality of teaching, knowledge control and training. Positive assessment (satisfaction is more than 50%) deserve: the organization and conditions of the educational process, the content of academic disciplines in all cycles, the quality of teaching, the volume and quality of the library fund. However, some comments revealed dissatisfaction with the technical means, the quality of the content audiences, the organization of pedagogic assistance and students’ self-directed learning, schedule of classes, quality of teaching materials, organization of traineeships, quality control test, availability of laboratories and computer classes outside the classroom.The assessment of the socio-cultural environment considered aspects of the organization of students’ extracurricular work, the socio-psychological climate; the conditions of life support of the educational process (sanitary and social); socio-cultural activities related to the satisfaction of spiritual and physical needs of an individual; socio-cultural fostering. The main comments are related to the quality of social and living conditions (catering, living conditions in a hostel).The results of the survey showed the need for further research in order to form a generalized (complex) model for assessing the quality of the University activities.